2010
DOI: 10.1038/labinvest.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arkadia on airway remodeling through enhancing TGF-β signaling in allergic rats

Abstract: Upregulation of transforming growth factor-b (TGF-b) signaling is interrelated with the development of airway remodeling. In this study, we examined the role of two E3 ubiquitin ligases, Arkadia and Smurf2, which are critically required for TGF-b signaling in airway remodeling. Rats were immunized with ovalbumin (OVA) and then challenged with an OVA aerosol. In in vitro experiments, normal human bronchial epithelial cells were stimulated with TGF-b 1 with or without the preincubation of Arkadia/Smurf2 small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Ski expression has been shown to inhibit vascular smooth muscle cell proliferation by suppressing Tgfb/Smad3 signaling but up-regulating p38 signaling [Li et al, 2013]. Activation of Tgfb signaling in OVA-sensitized and -challenged rats has been found to contribute to the pathogenesis of airway remodeling through the reduction of Ski proteins [Li et al, 2010]. We found CpG site-specific hypomethylation at Tgfβ2, Smad2 and Smad3 , and Ski hypermethylation in lung and MASMCs, which may be associated with HDM-induced AHR.…”
Section: Discussionmentioning
confidence: 99%
“…Ski expression has been shown to inhibit vascular smooth muscle cell proliferation by suppressing Tgfb/Smad3 signaling but up-regulating p38 signaling [Li et al, 2013]. Activation of Tgfb signaling in OVA-sensitized and -challenged rats has been found to contribute to the pathogenesis of airway remodeling through the reduction of Ski proteins [Li et al, 2010]. We found CpG site-specific hypomethylation at Tgfβ2, Smad2 and Smad3 , and Ski hypermethylation in lung and MASMCs, which may be associated with HDM-induced AHR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-142-3p can modulate ASMC phenotypes via a TGF-β-mediated mechanism [12]. One study suggested a close correlation between the activation of the TGF-β pathway and the pathogenesis underlying asthma-induced airway remodeling [13]. Epidermal growth factor receptor (EGFR) activation plays an essential role in the migration, differentiation and proliferation of numerous human epithelial cell types [14].…”
Section: Introductionmentioning
confidence: 99%
“…As aforementioned, Smurf2 and Arkadia were highly expressed in the renal tissues of DN rats in the present study. TGF-β enhances its biological effects by modulating the Arkadia-mediated SnoN degradation (29,30). Arkadia binds the SnoN protein with the carboxy-terminal RING domain (28) and induces ubiquitin-mediated degradation of the SnoN protein in the presence of p-Smad2/3 involvement (31).…”
Section: Discussionmentioning
confidence: 99%